Sex‐specific differences in reproductive life‐history traits of the moss Weissia jamaicensis. Issue 4 (18th April 2022) - Santos, Wagner L.; Pôrto, Katia C.; Pinheiro, Fabio
Abstract: Premise: We investigated sex‐specific differences in the life‐history traits of a metapopulation of the dioicous moss Weissia jamaicensis . Field observations revealed high rates of fertilization, which is uncommon for most dioicous bryophytes. We raised four hypotheses associated with the way the reproductive traits are related to the fertilization rate in this metapopulation. Methods: We sampled 10 patches of the metapopulation and quantified sexual expression, sex ratio, reproductive success, and reproductive allocation. The ramets were classified as male, non‐sporophytic female, sporophytic female, or non‐sex‐expressing. Thirty ramets from each of the categories expressing sex were placed for regeneration to test the effect of reproductive allocation on this trait. Results: We found greater expression of the female function in all patches, implying a female bias in the metapopulation. The number of male ramets was variable in each patch and did not affect reproductive success. At the prezygotic level, the allocation of resources to the male function was higher. However, the large allocation of resources to sporophyte development in sporophytic females, which exceeded allocations at prezygotic levels, was related to the higher mortality rate of these ramets, suggesting reproductive cost. Conclusions: The prezygotic ramets that allocated the greatest amount of resources to reproduction expressed sex less frequently, biasing the sex ratio toward the sex that allocated the least amount of resources to reproduction. Overall, the ramets that allocated the greatest amount of resources to reproduction had the lowest regeneration rate, suggesting reproductive cost.